Dietary habits and fluid intake of a group of elite Spanish basketball players: A need for professional advice? - Schröder, H.; Navarro, E.; Mora, J.; Seco, J.; Torregrosa, J. M.; Tramullas, A. (European Journal of Sport Science, 2004)
The aim of the present study was to analyse dietary habits and fluid intake of professional basketball players with consideration of dietary guidelines and sport nutrition recommendations. A dietary habit questionnaire including a 24 h recall was recorded by 55 elite basketball players of the first Spanish Basketball League. Energy consumption among these athletes was high 17.7 ±0.9 MJ · day--;1and 882 ±486 ml of liquids during training and competition session, respectively. Furthermore, 44 % of the participants recorded not to drink before getting thirsty and 3 athletes stated never to drink during training and 2 did so during competition. Results of the present study underline the need for professional advice from sport nutritionists for elite basketball players.